INTERNATIONAL RELATIONS DYNAMICS TOWARDS TURKEY’S MIGRATION POLICY REGARDING SYRIAN REFUGEE - Muhaimin Zulhair; Salma Rafifah (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2019)
Syrian refugee and asylum seeker have become a major topic in international migration over the past few years. The conflict that has not yet shown a sign of its end, makes millions of people left with no choice other than going out from their home town, as their home has become a warfare. Turkey is one of the countries that accepts most of this refugees and asylum seeker. Thus, this paper intended to analyze the reason behind this country’s policy regarding Syrian refugees and asylum seeker, by using the concept of the Factors Influencing the Policy Responses of Host Governments to Mass Refugee Influxes particularly the international relations variable. This paper proposed a research question, how the international relations has impacted Turkey’s policy in responding to Syrian refugees. This qualitative research data is gathered from the secondary sources. This study finds that international relations variable impacted the policy choice in the sense that the change in the relationship between Turkey and Syria, EU - Turkey as well as the norm and dynamic in international refugee regime resulted in the change of Turkey’s policy.